Предмет: Алгебра,
автор: AMK525
Упростите выражение и найдите его значение: (а+3) (а-10)-(а+7) (а-4),если а=-0,01
(8с+12) (3с-1)+(3с+2) (-5с-6),если с=1 1/3
Ответы
Автор ответа:
0
Автор ответа:
0
(а+3)(а-10)-(а+7)(а-4)=а² - 10а+3а -30 - а²+4а-7а+28= - 10а -2
при а= -0,01
-10*( -0,01) - 2=0,1 - 2= -1,8
.
(8с+12)(3с-1)+(3с+2)( -5с -6)=24с² - 8с+36с -12 -15с² -18с -10с -12=9с² - 24
при с=1 1/3
9 *(1 1/3)² - 24=9 * (4/3)² - 24=16-24= - 8
при а= -0,01
-10*( -0,01) - 2=0,1 - 2= -1,8
.
(8с+12)(3с-1)+(3с+2)( -5с -6)=24с² - 8с+36с -12 -15с² -18с -10с -12=9с² - 24
при с=1 1/3
9 *(1 1/3)² - 24=9 * (4/3)² - 24=16-24= - 8
Похожие вопросы
Предмет: Физика,
автор: Andrey55456
Предмет: Қазақ тiлi,
автор: zanataslan284
Предмет: География,
автор: Dimate9
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: 33708197512312345678